Land Management in Red (Chalka) Soils of Telengana - Chinnamani, S; Singh, Gurmel (Annals of Arid Zone, 2016)
Soil and water conservation and land use development is a necessity in modern agriculture. The results achieved at Soil Conservation Research, Demonstration and Training Centre, Ibrahimpatan, have revealed that implementation of modern agricultural technique coupled with cultivation of perennial grass and tree crops will improve the economy of the farmer of rainfed red soil region. Adoption of soil conservation measures like graded binding cultivation of high yielding crops, grasses and trees i. e., adoption of mixed farming is a must in the non irrigated red' soil regions of semi-arid tracts. For changing the dry lands into irrigated cultivable land grading has been found to be very useful for economy in water and obtaining high yield of crops on sustained basis.